Community health workers the Tanzanian experience - Heggenhougen, Kris. (Oxford Oxford University Press, 1987)
Community Health Workers: The Tanzanian Experience profiles the history, the present condition, and the future prospects of Tanzanian community health workers. Based on collaborative research and extensive surveys and interviews conducted by the authors from 1980 to 1983, this comprehensive work details the successes and shortcomings of Tanzania's program of primary health care, and provides a valuable example for the establishment of similar, and particularly larger, health care programs in East and South Africa and throughout the developing nations of the world. Primary health care professionals and students of public health administration will value this timely assessment of the state of Tanzania's community health services.
Includes index.
Keywords: Community Health Aides--Tanzania.